The Effect of Implementation of Quality Management Information Systems and Quality of Training on Employee Performance and Enjoyment as Intervening in Startup Companies - Nurcahyo, Nurwanto; Wibawanto, Sigit; Riatmaja, Dodi Setiawan; Ridanasti, Erlita (Fokus Bisnis Media Pengkajian Manajemen dan Akuntansi, 2022)
The purpose of this study was to determine the Effect of Quality Management Information System Applications and Quality Management Information System Application Training on Employee Performance Through Intervening Enjoyment Variables. To determine the effect of SIM application quality on employee performance, see the influence between training quality and employee performance, as well as the effect of SIM application quality and training quality on employee performance mediated by enjoyment. This research was conducted by taking 40 employees from Startup Employees in Yogyakarta, with random sampling. The calculation technique used in this research is a model of Multiple Linear Regression Analysis and path analysis. There is a positive and significant effect of the Quality Management Information System Application on Enjoyment. There is a positive and significant influence on the Quality of Management Information System Application Training variable on Enjoyment. There is a significant effect of the Quality of Management Information System Application and Quality of Management Information System Application Training on Enjoyment. There is a positive and significant effect of the Quality Management Information System Application variable on Employee Performance. There is no significant effect of the variable of Quality Management Information System Application Training on Employee Performance.